Past form of modals in non-past contexts: a semiotic analysis - Hashim, Siti Afifah; Govindasamy, Subramaniam (Elsevier, 2015)
There has long been a misconception among second-language (L2) users that past forms (V+ed) only appear in past contexts indicating events that occur in the past. However, when authentic texts are analysed, one encounters a considerable use of past forms (V+ed) in non-past contexts. This study seeks to examine the occurrence of past forms in non-past contexts (which may eventually give different contextual messages) and to postulate an invariant meaning for this past form. Ten journalistic articles from The Economist were analysed. Modals were categorized according to the immediacy function they were performing. The study shows that past form in English does not only indicate past events but also conveys other contextual messages when it appears in non-past contexts. It was also discovered that there is only one invariant meaning for the past form used in non-past contexts.